(untitled) (Eurasian Research Bulletin, 2023)
Analysis of transfer pricing methods and the possibilities of their implementation in the activities of economic entities is the most important task to ensure fairness and transparency of cross-border transactions between related parties. Transfer pricing refers to the price at which related parties transact with each other. There are several methods for determining transfer prices, including the comparable uncontrolled price method, the cost-based method, the resale price method, and the profit-based method. Each method has its own characteristics and applicability in different situations. This may include documentary analysis, collection and analysis of data on market prices and the competitive environment, as well as risk assessment and application of appropriate transfer pricing methods. The introduction of effective transfer pricing methods can help prevent tax evasion and ensure a fair distribution of tax liabilities between related enterprises. However, this can also create challenges and require additional resources and expertise to properly apply methods and comply with tax laws